FaktorâFaktor Yang Mempengaruhi Prestasi Kerja (Studi Pada Karyawan Kantor Kementrian Agama Provinsi Jawa Tengah) - Suprihatiningrum, Hesti; Bodroastuti, Tri (Jurnal Kajian Akuntansi dan Bisnis, 2012)
Employee achivement is an achivement reached by somebody troughthe work behavior ini carrying out work activities. Achvement is a record of the resultsgained trough cartain function of work in a certain period of time. Therefore an employeeshould have achivement measure for his employees. The information of employeeachivement is needed if the employer would like to change the prevailed system. We areoften trapped to evaluate an employee with his work, while system or device doesnât meetthe standart. The purpose of this research was to find out the influence of motivation,work satisfaction, stres level, job physical condition, compensation system and jobdesign toward work achievement in Religion Ministry office of Central Java province.The population in this research was 230 employess with sample total that was used as bisas 70 employess. The technique sampling used was convenience sampling that istechnique sampling based on ease. The analysis tool used was multiple linier regression,which was firstly examined by validity and reability. The research result showed thatmotivation, work satisfaction, stres level, job physical condition, compensation systemand job design influenced significantly work achievement of employees at ReligionMinistry of central Java Province both partial and simultaneous.Keywords: motivation, work satisfaction, stres level, job physical condition, compensationsystem and job design influenced significantly work achievement of employees.